Estimation of Stature from Finger Length Based on the Correlation - Yadav, Shekhar Kumar; Shakya, Shuvechha (Journal of KIST Medical College, 2020)
Introduction: Estimation of stature is of paramount importance in verifying the identity of an individual from the bodily remains, often after any kind of mass disaster, explosion or intentional cuts and dismantling we encounter very few bodily parts. The objective of the present study was to estimate stature from the measurement of finger length based on the principle of correlation. Methods: The present study consisted of 300 individuals (150 male and 150 female) of age group 18 to 26 years during the period of August 2017 to August 2018. Stature and finger length of individuals were measured by using stadiometer and digital caliper respectively. Data were analyzed by using statistical software SPSS-22. Results: A positive and highly significant (p<0.01) correlation was observed in both genders. Linear regression equation for stature estimation was derived using finger length and checked for their accuracy by comparing the estimated stature to measured stature. The result shows no significant difference between estimated and measured stature. Conclusions: The results indicate that the finger length provides reliable means of estimating the stature of an unknown individual based on the principle of correlation. Hence it can be of significant help in establishing the identity of an individual.